2014
DOI: 10.1088/2041-8205/783/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of White Dwarf Companions to Blue Stragglers in the Open Cluster NGC 188: Direct Evidence for Recent Mass Transfer

Abstract: Several possible formation pathways for blue straggler stars have been developed recently, but no one pathway has yet been observationally confirmed for a specific blue straggler. Here we report the first findings from a Hubble Space Telescope ACS/SBC far-UV photometric program to search for white dwarf companions to blue straggler stars. We find three hot and young white dwarf companions to blue straggler stars in the 7-Gyr open cluster NGC 188, indicating that mass transfer in these systems ended less than 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 29 publications
5
100
0
1
Order By: Relevance
“…V228 in 47 Tuc, Kaluzny et al 2007) and those have finished mass transfer (e.g. WOCS 4348, 4540 and 5379 in NGC 188, Gosnell et al 2014). The blue-straggler binaries during the mass-transfer phase have a "low-luminosity boundary" (about 0.75 mag brighter than the ZAMS) given by Tian et al (2006), and can match the observed red-sequence blue stragglers in globular cluster M30 (Ferraro et al 2009;Xin et al 2015).…”
Section: Introductionmentioning
confidence: 69%
“…V228 in 47 Tuc, Kaluzny et al 2007) and those have finished mass transfer (e.g. WOCS 4348, 4540 and 5379 in NGC 188, Gosnell et al 2014). The blue-straggler binaries during the mass-transfer phase have a "low-luminosity boundary" (about 0.75 mag brighter than the ZAMS) given by Tian et al (2006), and can match the observed red-sequence blue stragglers in globular cluster M30 (Ferraro et al 2009;Xin et al 2015).…”
Section: Introductionmentioning
confidence: 69%
“…First, Santana et al (2013) showed observationally that the fraction of blue stragglers in dwarf galaxies can be of the order of 10× higher than those in globular clusters, which, according to the authors, is because of the higher prevalence of binaries from which blue stragglers are formed in the low-density environments present in local dSph galaxies. Second, Milky Way globular clusters are old stellar populations (older than ∼10-11 Gyr according to recent reviews such as Gratton et al 2012 Gosnell et al (2014) have confirmed the presence of three hot and young white dwarfs as companion stars in binary systems for three blue straggler stars in the open cluster NGC188. These white dwarfs would correspond to former RGB or AGB stars that transferred mass in the recent past to their companion stars in the binary system, hence transforming them into blue stragglers.…”
Section: Young Population Versus Blue Straggler Populationmentioning
confidence: 96%
“…Recently, Gosnell et al (2014Gosnell et al ( , 2015 used HST to study BSSs in NGC188 in the UV region, detecting white dwarf (WD) companions to seven BSS and thereby confirming that at least some BSSs can form by mass transfer. Three of their BSSs were found to have cool WD companions; four were found to have hotter WDs.…”
Section: Arxiv:161202535v1 [Astro-phsr] 8 Dec 2016mentioning
confidence: 99%